PERENCANAAN PEMBELAJARAN MELALUI STRATEGI INTEGRASI SISTEM DAN TEKNOLOGI INFORMASI PADA SD ISLAM AL-FALAH JAMBI - Mahyudin Mahyudin; Noer Suhartina (Universitas Batanghari Jambi, 2018)
Al-Falah Jambi Islamic Primary School (SDI Al-Falah Jambi) is the best Moslem Primary School which is located in Jambi City with many prestation, although SDI Al-Falah Jambi do not applicate integration information system for learning activities through multimedia and online because human capital is not capable. This research purpose is analysis learning plan through information technology and system integration strategy in the SDI Al-Falah Jambi.Research time was done on October 2016 in SDI Al-Falah Jambi. Indeed sampling technique was purposive sampling. Research result shownthatSDI Al-Falah Jambi do not have facilities and equipment that match for supporting learning activities through multimedia and online information technology and system integration, and architecture development proposal in SDI Al-Falah Jambi are organitation, business, data, technology, and solution.Keywords : Multimedia, Online, Planning, Learning